Spatial separation enhances speech intelligibility but increases listening effort with session-dependent variability in pupillometric measures - Thakkar, Tanvi; Knoepker, Jarett; Dennison, Stephen R.; Roche, Joseph P.; Litovsky, Ruth Y. (Frontiers in Neuroscience, 2025)
IntroductionThe current understanding of the cognitive load of listening effort has been advanced by combining speech intelligibility and pupillometry measures. However, the reliability of pupil dilation metrics in complex listening scenarios like spatial release from masking (SRM) remains uncertain. This study investigated how spatial separation of sound sources impacts listening effort (via peak pupil dilation, PPD) and speech intelligibility.MethodsSpeech intelligibility and listening effort were simultaneously measured under co-located and symmetric, spatially-separated conditions at varying signal-to-noise ratios (SNRs).ResultsResults showed that although spatial separation improved speech intelligibility, it did not yield a corresponding reduction in listening effort. Instead, listening effort increased as SNR became more challenging. Furthermore, test–retest reliability was moderate-to-high for speech intelligibility but only moderate-to-low for PPD, with greater consistency observed at more challenging SNRs. These results suggest that obtaining stable PPD measures within an SRM paradigm may be difficult to achieve.DiscussionThese findings indicate that obtaining stable PPD measures within an SRM paradigm can be challenging. Test session reliability is weak when combining SRM paradigms with measures of listening effort, which may reduce statistical power due to factors such as sample size, number of trials, and sessions tested. This is further limited by the relatively small and homogeneous sample of young, typical hearing adults. Future studies should include a larger and more diverse participant group to assess the generalizability of these results.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT02532972.